Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.375
|View full text |Cite
|
Sign up to set email alerts
|

Do Neural Language Models Show Preferences for Syntactic Formalisms?

Abstract: Recent work on the interpretability of deep neural language models has concluded that many properties of natural language syntax are encoded in their representational spaces. However, such studies often suffer from limited scope by focusing on a single language and a single linguistic formalism. In this study, we aim to investigate the extent to which the semblance of syntactic structure captured by language models adheres to a surface-syntactic or deep syntactic style of analysis, and whether the patterns are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 20 publications
(27 reference statements)
1
41
2
Order By: Relevance
“…Probing results are somewhat dependent on the choice of linguistic formalism used to annotate the data, as Kulmizev et al (2020) found for syntax, and Kuznetsov and Gurevych (2020) found for se-mantic roles. Miaschi et al (2020) examined the layerwise performance of BERT for a suite of linguistic features, before and after fine tuning.…”
Section: Probing Lms For Linguistic Knowledgementioning
confidence: 94%
“…Probing results are somewhat dependent on the choice of linguistic formalism used to annotate the data, as Kulmizev et al (2020) found for syntax, and Kuznetsov and Gurevych (2020) found for se-mantic roles. Miaschi et al (2020) examined the layerwise performance of BERT for a suite of linguistic features, before and after fine tuning.…”
Section: Probing Lms For Linguistic Knowledgementioning
confidence: 94%
“…For example, they could be interfaced with large-scale pretrained models such as BERT (Devlin et al 2019) and GPT (Radford et al 2019), thereby fusing together deep contextual representations and rich semantic symbols (see Figure 3). Aside from enriching pretrained models (Wu and He 2019; Hardalov, Koychev, and Nakov 2020; Kuncoro et al 2020), such representations could further motivate future research on their interpretability (Wu and He 2019;Hardalov, Koychev, and Nakov 2020;Kuncoro et al 2020;Hewitt and Manning 2019;Kulmizev et al 2020).…”
Section: Universal Drssmentioning
confidence: 99%
“…Little direct work exists on extensive empirical investigations between UD and SUD with parsers. Recent work by Kulmizev et al (2020) performed probing experiments across a set of languages to extract dependency graphs from BERT (Devlin et al, 2019) and ELMO (Peters et al, 2018) language models, finding that both models prefer UD, with tree shape directly correlated to preference strength.…”
Section: Related Workmentioning
confidence: 99%